Mastering Arabic Through the Contextual Teaching and Learning Model at Thamavitya Mulniti School Thailand - Wildatul Muyasaroh; Boby Bagas Purnama; Agung Setiyawan; Wildatul Muyasiroh; Dika Armyni; Shamimi Binti Azhar (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
Arabic language learning in minority Muslim communities, such as in Thailand, faces significant challenges, including the limited use of Arabic in daily life and less innovative teaching methods. One approach considered effective in increasing students' interest and understanding is Contextual Teaching and Learning (CTL), which connects learning with students' real-life experiences. This study aims to explore the implementation of the CTL model in Arabic language learning at Thamavitya Mulniti School, Thailand, and identify the challenges faced in its application. This research employs a qualitative approach using a case study method. Data were collected through interviews, observations, and document analysis involving teachers, students, and the school's curriculum. Data analysis was conducted using Miles and Huberman's model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of CTL in this school has covered almost all key components of the model, such as constructivism, inquiry, questioning, modelling, reflection, and authentic assessment. However, there are still obstacles in the application of the learning community component, which hinders Arabic language interaction among students. This study recommends optimizing the learning community aspect, utilizing technology-based learning media, and improving facilities to support the successful implementation of CTL.